SUBJECT: VIABILITY OF DUST GRAINS IN SUGAR BEET VARIETIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article presents data on the viability of pollen grains of samples of sugar beet cultivars selected as primary parental forms. Studying and researching the viability of plant pollen grains is of great importance in solving many problems of practical breeding. Pollen grains, dust particles (palynology) are grains formed in pollen grains of flowers. It develops from a microspore in a microsporangium. Pollen grains have outer (exina) and inner (intina) membranes. Depending on the type of plant, the shape and size of the dust grains are different.